The Walsh Family Resilience Questionnaire: the Italian version - Rocchi S (Dove Medical Press, 2017)
Silvana Rocchi,1 Claudio Ghidelli,2 Roberto Burro,3 Michele Vitacca,4 Simonetta Scalvini,5 Anna Maria Della Vedova,6 Gianmarco Roselli,7 Jean-Pierre Ramponi,8 Giorgio Bertolotti9 1Psychology Service, ICS Maugeri Spa SB, Institute of Lumezzane, 2Psychological Counselling Service, Università Cattolica del Sacro Cuore, Brescia, 3Department of Human Sciences, University of Verona, Verona, 4Respiratory Rehabilitation Division, 5Cardiac Rehabilitation Division, ICS Maugeri Spa SB, Institute of Lumezzane, 6Department of Clinical and Experimental Sciences, University of Brescia, 7Department of Mental Health, Spedali Civili, 8ICS Maugeri Spa SB, Institute of Lumezzane, Brescia, 9Psychology Unit, ICS Maugeri Spa SB, Institute of Tradate, Varese, Italy Background: Resilience focuses on strength under stress, in the context of adversity. Walsh’s theoretical model identifies relational processes that allow families to tackle and overcome critical situations, dividing them into three domains of family function. The aim of this study was to assess resilience in families of patients with a chronic disease by adapting and validating the Italian version of the Walsh Family Resilience Questionnaire (Walsh-IT). Patients and methods: An Italian adult sample of 421 participants (patients and relatives) was collected with the aim to assess the reliability and validity of the Walsh-IT. Concurrent validity was carried out by comparing this instrument with the Family Adaptability and Cohesion Evaluation Scale III (FACES III) administered at the same time as the Walsh-IT. Results: Reliability showed high correlation between repeated measurements. The alpha coefficient was 0.946. Both parallel analysis and minimum average partial criteria suggested that the best number of domains is equal to 3, explaining 50.4% of the total variance. Based on the results obtained from the Rasch analysis, items 10, 11, 16, 22, and 23 have been removed resulting in a short-form questionnaire (Walsh-IT-R) of 26 items with three domains: shared beliefs and support (SBS, α=0.928); family organization and interaction (FOI, α=0.863); and utilization of social resources (USR, α=0.567). The total score of the Walsh-IT-R was strongly correlated with the total score of FACES III Real Family Scale (r=0.68; p<0.0001). Conclusion: Results support that the Walsh-IT-R is a valid instrument for the assessment of family resilience in Italy when contending with the challenges of chronic disease. It could be used in pre- and post-assessment in practice effectiveness research, offering a profile of family resilience processes at the start and end of interventions and follow-up. Keywords: family resilience, chronic illness, assessment, Rasch model, family functioning